Smoking and periodontal microorganisms. Issue 1 (November 2019) - Hanioka, Takashi; Morita, Manabu; Yamamoto, Tatsuo; Inagaki, Koji; Wang, Pao-Li; Ito, Hiroshi; Morozumi, Toshiya; Takeshita, Toru; Suzuki, Nao; Shigeishi, Hideo; Sugiyama, Masaru; Ohta, Kouji; et al.
Summary: Resolution of dysbiosis following treatment for periodontal disease and tobacco dependence has been reported in longitudinal intervention studies. In the present report, we evaluated the biological findings regarding the effect of smoking on the periodontal microbiome. A standardized electronic search was conducted using MEDLINE; overall, 1099 papers were extracted. Studies that addressed the relationship between tobacco and periodontal pathogens were included. Finally, 42 papers were deemed appropriate for the present review. Functional changes in periodontal pathogens exposed to nicotine and cigarette smoke extract support the clinical findings regarding dysbiosis of the subgingival microbiome. Dysbiosis of the periodontal microbiome was presented in smokers regardless of their periodontal condition (healthy, gingivitis, or periodontitis) and remained significant only in smokers even after the resolution of experimentally-induced gingivitis and following reduction of clinical signs of periodontitis with non-surgical periodontal treatment and over 3 months post-therapy. Based on these findings, smoking cessation in periodontitis patients is beneficial for promoting a health-compatible subgingival microbial community. To maximize the benefits of these interventions in dental settings, further studies on periodontal microbiome are needed to elucidate the impact of tobacco intervention on preventing recurrence of periodontal destruction in the susceptible subjects.